Factorial analysis application to organizational public data for explaining the disclosure of environmental information (2023)
The articles objective is to analyze the dimensions of information disclosure related to corporate environmental sustainability. For this, public data from 100 Colombian companies were used, and an indicator was applied to assess environmental information disclosure. The study applied Principal Component Analysis (PCA), measures of central tendencies, and dispersion. It was designed as longitudinal research with a quantitative approach, explanatory scope, and non-experimental. The results prove the effectiveness of the PCA applied to public data, to address problems in the disclosure of environmental information at the organizational level. In parallel, it is evident that the dimension "Water" is the most relevant followed by the dimensions "Materials", "Emissions" and "Energy". These results allow us to conclude that the interested parties assign relevance in the same order they appear, which largely explains the disclosure of information related to organizational environmental sustainability.